An evaluation of the effect of a patient education programme on the eventual quality of life of the laryngectomy patient - Stellenberg, Ethelwynn L.(Ethelwynn Linda) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Cur.) -- University of Stellenbosch, 1995.